Seeking Wisdom in Adult Teaching and Learning An Autoethnographic Inquiry - Fraser, Wilma (Palgrave Macmillan UK, 2018)
This book concerns the pursuit of wisdom in education, and the argument that wisdom - personified here as Sophia - is tragically marginalised or absent in current Western epistemological discourses. It includes a review of key historical and classical framings which have lost much potency and relevance as certain cultural narratives hold sway; these include the reductionist, technicist and highly instrumentalist discourses which shape the articulation and delivery of much education policy and practice, whilst reflecting similar troubling framings from broader neoliberal perspectives. Fraser argues that wisdom's marginalisation has had, and continues to have, profoundly deleterious consequences for our educative practices. Through a compelling combination of narrative and autoethnographic techniques, while also drawing on philosophical and cultural traditions, the book pushes at the boundaries of emerging knowledge, including how knowledge is generated. It will be of interest to those who facilitate the learning of adults in a variety of settings as well as to students and supervisors seeking exemplars and 'justification' for working in non-traditional ways. .